2017
DOI: 10.1002/cpt.622
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physiologically Based Pharmacokinetic Models on Regulatory Reviews and Product Labels: Frequent Utilization in the Field of Oncology

Abstract: Physiologically based pharmacokinetic (PBPK) modeling can be used to predict drug pharmacokinetics in virtual populations using models that integrate understanding of physiological systems. PBPK models have been widely utilized for predicting pharmacokinetics in clinically untested scenarios during drug applications and regulatory reviews in recent years. Here, we provide a comprehensive review of the application of PBPK in new drug application (NDA) review documents from the US Food and Drug Administration (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 4 publications
2
53
0
Order By: Relevance
“…Another trend evident from our survey and also consistent with findings in another recent survey is that PBPK modeling and simulation is increasingly accepted by the FDA to inform clinical DDI risk in product labeling, provided that PBPK models are first qualified with PK data from one or more clinical studies designed to evaluate the worst‐case scenario with respect to DDIs or drug‐genotype interactions (e.g., DDI study with a strong CYP inhibitor or inducer, or study assessing genotype‐PK relationships in extensive vs. poor metabolizers) . In this context, PBPK modeling and simulation can subsequently be used to predict lower‐risk scenarios (e.g., the effect of moderate inhibitors or inducers or intermediate metabolizers) and support labeling statements related to DDI risk.…”
Section: Lessons Learned For Anticancer Drug Developmentsupporting
confidence: 82%
“…Another trend evident from our survey and also consistent with findings in another recent survey is that PBPK modeling and simulation is increasingly accepted by the FDA to inform clinical DDI risk in product labeling, provided that PBPK models are first qualified with PK data from one or more clinical studies designed to evaluate the worst‐case scenario with respect to DDIs or drug‐genotype interactions (e.g., DDI study with a strong CYP inhibitor or inducer, or study assessing genotype‐PK relationships in extensive vs. poor metabolizers) . In this context, PBPK modeling and simulation can subsequently be used to predict lower‐risk scenarios (e.g., the effect of moderate inhibitors or inducers or intermediate metabolizers) and support labeling statements related to DDI risk.…”
Section: Lessons Learned For Anticancer Drug Developmentsupporting
confidence: 82%
“…The flexible applicability of PBPK modeling during the course of drug development programs is also reflected in the increased number of submissions to the Food and Drug Administration (FDA) containing PBPK applications . Accordingly, in their draft guidance on pediatric clinical studies, the FDA advocates the use of modeling and simulation during the drug development process to support dose selection and/or study design, data analysis, and interpretation for planned pediatric studies .…”
mentioning
confidence: 99%
“…The flexible applicability of PBPK modeling during the course of drug development programs is also reflected in the increased number of submissions to the Food and Drug Administration (FDA) containing PBPK applications. [5][6][7] Accordingly, in their draft guidance on pediatric clinical studies, the FDA advocates the use of modeling and simulation during the drug development process to support dose selection and/or study design, data analysis, and interpretation for planned pediatric studies. 8 Additionally, in the case of rare pediatric diseases, the FDA draft guidance stipulates that a mechanism-based approach, such as PBPK modeling, should play a key role for dose characterization and that whenever new studies in children are deemed necessary, modeling and simulation approaches should be used to optimize pediatric studies (eg, design, sample size, starting doses, timing of sampling, and number of samples).…”
mentioning
confidence: 99%
“…In another study, a CART-cell therapy restricted the growth of pancreatic tumours in all treated mice to below the limit of detection with a dose of 10 7 cells (equivalent to 4.5×10 10 in humans) [43]. In the clinic, a study of CEA CART-cells against colorectal cancer [44] escalated doses between 10 7 and 10 10 . The authors found that the lower doses did not stop tumour progression (in 3 of 14 of presented patients) and higher doses achieved only stable disease.…”
Section: Species-specific Delivery Rates and Dosage Scalingmentioning
confidence: 99%
“…Systematic quantitation of the variation of vascular delivery rates across organs, tumour types and species will improve understanding of comparative preclinical and clinical outcomes and inform improved dosing strategies. Physiologically-based pharmacokinetic modelling (PBPK) has been used extensively to predict drug concentration profiles and their variability across different tissues and individuals, to estimate the efficacy of clinical dosing regimens (for recent reviews, see [10][11][12]). PBPK models have been used in drug development since 2000 and are readily accepted as providing supporting information by both the US Food and Drug Administration and the European Medicines Agency.…”
Section: Introductionmentioning
confidence: 99%